Relationship of Tricuspid Repair at the Time of Left Ventricular Assist Device Implantation and Survival. Issue 11 (November 2014) - Brewer, Robert J.; Cabrera, Rafael; El-Atrache, Mazen; Zafar, Amna; Hrobowski, Tara N.; Nemeh, Hassan M.; Selektor, Yelena; Paone, Gaetano; Williams, Celeste T.; Velez, Mauricio; Tita, Cristina; Morgan, Jeffrey A.; et al.
Purpose: Tricuspid regurgitation contributes to right ventricular failure (RVF) and is associated with worse clinical outcomes in patients undergoing left ventricular assist device (LVAD) treatment. However, whether tricuspid valve repair (TVR) at the time of LVAD implantation improves outcomes is not clear. Methods: We identified all patients undergoing initial implantation of a long-term continuous-flow LVAD at our institution from March 2006 to August 2011. We assessed the impact of TVR on survival and incidence of RVF using Kaplan-Meier curves and proportional hazards regression adjusted for age, gender, baseline tricuspid regurgitation, RV function, MELD score, albumin, and indication (bridge vs. destination). Results: A total of 101 patients were included in the analysis, of which 14 patients underwent TVR concomitant LVAD. All TVR patients had moderate or severe baseline regurgitation. Crude survival was not different between groups. In multivariable models adjusted for confounding factors, TVR showed a significant association with improved survival (HR = 0.1, p = 0.049). Adjusted models showed no difference in RVF. Conclusions: In this cohort of patients, TVR at the time of LVAD implantation appears associated with better survival. Additional larger studies are needed to verify the effect of TVR at the time of LVAD implantation, and whether it should be utilized more frequently.